Spartan gold - Cussler, Clive; Blackwood, Grant; Brick, Scott ([New York] : Penguin Audio, 2009)
Thousands of years ago, the Persian king Xerxes the Great was said to have raided the Treasury at Delphi, carrying away two solid gold pillars as tribute. In 1800, Napoleon Bonaparte and his army stumble across the pillars in the Pennine Alps. Unable to transport them Napoleon creates a map on the labels of twelve bottles of rare wine. And when Napoleon dies, the bottles disappear. Treasure hunters Sam and Remi Fargo are exploring the Great Pocomoke Swamp in Delaware when they are shocked to discover a World War II German u-boat. Inside, they find a bottle taken from Napoleon's 'lost cellar.' Fascinated, the Fargos set out to find the rest of the collection. But another connoisseur of sorts has been looking for the bottle they've just found. He is Hadeon Bondaruk - a half- Russian, half-Persian millionaire. He claims to be a descendant of King Xerxes himself. And he wants his treasure back.
Unabridged.
Compact discs.
Read by Scott Brick.
Keywords: Treasure troves -- Fiction; Audiobooks; Adventure fiction; Suspense fiction